A double‐blind placebo‐controlled clinical trial testing the effect of hyperbaric oxygen therapy on brain and cognitive outcomes of mildly cognitively impaired elderly with type 2 diabetes: Study design. Issue 1 (13th April 2020) - BenAri, Ori; Efrati, Shai; Hadanny, Amir; Sano, Mary; Bendlin, Barbara B.; Lin, HungMo; Liu, Xiaoyu; Sela, Inbar; Almog, Ganit; Livny, Abigail; Sandler, Israel; Ben‐Haim, Simona; et al.
Abstract: Introduction: Type 2 diabetes (T2D) is a risk factor for dementia. Ischemia due to vascular pathology is hypothesized to be an underlying mechanism for this association. Hyperbaric oxygen therapy (HBOT) is a treatment in which oxygen‐enriched air (up to 100%) is administered to patients in a chamber at a pressure above one atmosphere absolute. HBOT is approved for the treatment of T2D ischemic non‐healing wounds. Evidence from animal studies and small clinical trials suggests that HBOT improves hypoxic/ischemic brain injuries, consequently inducing brain angiogensis, leading to cognitive improvement. Methods: We present the design of the first double‐blind, placebo‐controlled, clinical trial on brain and cognitive outcomes in elderly (n = 154) with T2D and mild cognitive impairment to compare the effects of HBOT versus sham (normal air with 1.1 ATA pressure in the first and last 5 minutes of the session). Eligible candidates are randomized with equal probability to HBOT and sham. Outcomes are assessed before and after treatment, and at 6‐ and 12‐month follow‐up. The primary cognitive outcome is global cognitive change, indexed by a composite sum of z‐scores of four executive functions and four episodic memory tests. The primary neurobiological outcome is cerebral blood flow (CBF; via arterial spin labeling magnetic resonance imaging [ASL‐MRI]) and cerebral glucose utilization via fluorodeoxyglucose positron emission tomography (FDG‐PET). Secondary outcome measures are specific cognitive domains (executive function and episodic memory) and functional measures (Clinical Dementia Rating sum of boxes, activities of daily living). Efficacy analyses will be performed for the intent‐to‐treat sample. Discussion: Recent studies suggest that HBOT induces neuroplasticity and improves cognition in post‐stroke and traumatic brain injury patients. However, its effect on cognition, cerebral blood flow, and brain glucose utilization in T2D patients at high dementia risk is yet to be determined. If effective, this study may provide strong evidence for the brain and cognitive benefits of HBOT in this population.